2012
DOI: 10.1108/10309611211244519
|View full text |Cite
|
Sign up to set email alerts
|

Desirable generic attributes for accounting graduates into the twenty‐first century

Abstract: Purpose -The purpose of this paper is to determine the requirements of accounting graduates in relation to generic attributes. Employers have consistently maintained that graduates are deficient in this area. This Australia-wide, all-sector study addresses the issue by examining what employers mean when they make demands for universities and academics to deliver work-ready graduates. Design/methodology/approach -Interviews (recorded, transcribed and analysed with NVivo) with employers, and accounting professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 24 publications
9
121
1
8
Order By: Relevance
“…The findings from the ALTC study were published by Tempone et al. () confirming the non‐technical skills identified in Volume 1 of the ALTC report and described by Tempone et al. as generic attributes for accounting graduates.…”
Section: Prior Literaturesupporting
confidence: 73%
“…The findings from the ALTC study were published by Tempone et al. () confirming the non‐technical skills identified in Volume 1 of the ALTC report and described by Tempone et al. as generic attributes for accounting graduates.…”
Section: Prior Literaturesupporting
confidence: 73%
“…The same goes for the United Kingdom as Martin, Villeneuve-Smith, Marshall and Mckenzie (2008) list timekeeping, literacy and numeracy, eagerness and dedication, communication, and personal presentation skills as attributes most sought after by employers. In Australia, a study by Tempone et al (2012) suggested that employers require graduates to possess communication, teamwork and self-management skills.…”
Section: Lecturersmentioning
confidence: 99%
“…Terminologies commonly used are words such as transferrable skills, key skills, soft skills, generic attributes, employability skills, key competencies, core skills, and underpinning skills. In most cases, these terms are used interchangeably to refer to graduate employability (Tempone et al 2012). …”
Section: Conceptualising Graduate Employability Attributesmentioning
confidence: 99%
“…Educators can also enlist the assistance of employers of accounting graduates to inform and reinforce the significance of listening to students. Presentations and guest lectures by employers are examples of interrelated contributions under the proposed integrated stakeholder approach that emphasise to students the importance of listening in practice and its status as a desirable graduate attribute (Tempone et al, 2012).…”
Section: Informing and Reinforcing The Importance Of Listeningmentioning
confidence: 99%